2002
DOI: 10.1091/mbc.01-08-0401
|View full text |Cite
|
Sign up to set email alerts
|

The Bending Rigidity of Mitotic Chromosomes

Abstract: The bending rigidities of mitotic chromosomes isolated from cultured N. viridescens (newt) and Xenopus epithelial cells were measured by observing their spontaneous thermal bending fluctuations. When combined with simultaneous measurement of stretching elasticity, these measurements constrain models for higher order mitotic chromosome structure. We measured bending rigidities of B ϳ10 Ϫ22 N ⅐ m 2 for newt and ϳ10 Ϫ23 N ⅐ m 2 for Xenopus chromosomes extracted from cells. A similar bending rigidity was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 25 publications
8
60
1
Order By: Relevance
“…A number of results indicate there is no appreciable restructuring of chromatin during or shortly after chromosome extraction into extracellular buffer. First, elasticity of chromosomes in the extracellular medium (17,18) is close to that measured in vivo (19,22,23). Second, we observe no morphological change of chromosomes during extraction from cytoplasm to extracellular buffer (17)(18).…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…A number of results indicate there is no appreciable restructuring of chromatin during or shortly after chromosome extraction into extracellular buffer. First, elasticity of chromosomes in the extracellular medium (17,18) is close to that measured in vivo (19,22,23). Second, we observe no morphological change of chromosomes during extraction from cytoplasm to extracellular buffer (17)(18).…”
Section: Methodssupporting
confidence: 77%
“…However, such ''lost'' protein structures do not contribute significantly to the mechanical properties of mitotic chromosomes, because their bending and stretching properties in vivo are similar to those measured in the extracellular medium (23). Repetition of the experiments of this paper in mitotic cell extracts may be able to further address this question.…”
Section: There Is No Contiguous Protein Scaffold Within Mitotic Chrommentioning
confidence: 88%
“…Furthermore, chromosome bending requires a lateral deformation of the chromosome (figure 5d), but again according to the multilayer chromosome model, presumably this local deformation gives rise to the dissociation of nucleosome-nucleosome interactions between layers. As this mechanism is equivalent to the mechanism of elongation, this can explain the experimental results obtained with N. viridescens and X. laevis chromosomes [35] showing that the Young modulus calculated from bending results is equivalent to that found in stretching experiments.…”
Section: Consistency Test For the Proposed Supramolecularsupporting
confidence: 70%
“…Experimental data bearing on the second issue are somewhat contradictory. Simple in vitro bending and stretching experiments seem to indicate a thin, stiff core at the center of the chromosome (28), but later in vivo experiments are in good agreement with the predictions of a homogenous chromosome (26), like that considered here.…”
Section: Modelsupporting
confidence: 79%
“…With regard to the first issue, experimental studies have shown that for chromosomes of both newt lung epithelial cells and Xenopus A6 cells the bending and stretching moduli are roughly uniform along the length of the chromosome and are, in particular, no different in the vicinity of the centromere than elsewhere on the chromosome (26). Of course, the situation in Drosophila early embryos may be different, and studies of chromosome flexibility in Drosophila were unable to rule out this possibility (27).…”
Section: Modelmentioning
confidence: 99%